Effect of tenoxicam on biochemical serum parameters of rats - (:unkn) unknown (Freund Publishing House Ltd, 1999)
Tenoxicam is a nonsteroidal analgesic of the oxicam group, which possesses both antipyretic and anti-inflammatory characteristics. The use of tenoxicam has recently increased and it is reported in the literature that treatments lasting between a few weeks to three months caused increases in serum alanine transferase (ALT), aspartate transferase (AST), gamma glutamyl transferase (GGT) and bilirubin in humans. Toxic dose treatments to rats caused alterations in renal parameters. To verify these observations, various biochemical parameters were examined following administration of nontoxic doses of tenoxicam to rats. Rats were divided into three groups. One group received tenoxicam 0.6 mg/kg/day; the second group received 1.2 mg/kg/day i.p. The control group received normal saline i.p. At the end of 15 days, blood samples from the animals' hearts were taken for routine biochemical tests. No statistically significant changes were observed in serum urea, uric acid, creatinine, electrolytes, ALT, AST, total protein, bilirubin or glucose levels between the treatment groups and control groups. Increases in GGT levels were found to be statistically significant in both of the treatment groups compared with the control group.
Keywords: Biochemical parameters; Gamma-glutamyl transferase; Rat; Tenoxicam